Serum levels of sclerostin in cardiometabolic disorders during pregnancy. Issue 2 (December 2015) - Platz, Martin; Stepan, Holger; Schrey, Susanne; Kralisch, Susan; Wurst, Ulrike; Lossner, Ulrike; Jessnitzer, Beate; Kratzsch, Jürgen; Stumvoll, Michael; Fasshauer, Mathias; Ebert, Thomas
Abstract Objective Sclerostin has recently been introduced as a novel osteocyte-secreted factor which is associated with an adverse metabolic profile. However, regulation of circulating sclerostin in cardiometabolic disorders during pregnancy including gestational diabetes mellitus (GDM) and preeclampsia (PE) has not been comprehensively assessed, so far. Methods Serum levels of sclerostin were quantified in 72 women with GDM and in 72 healthy, pregnant, gestational age-matched controls (study population 1). Furthermore, circulating sclerostin was assessed in 51 women with PE as compared to 51 pregnant controls in a second cohort (study population 2). Results In the first study population (GDM), median [interquartile range] sclerostin levels were not significantly different in women with GDM as compared to controls (GDM: 19.2 [8.1] pmol/l; controls: 18.6 [7.1] pmol/l; p = 0.906). Interestingly, C reactive protein was a negative and independent predictor of circulating sclerostin in the GDM cohort in multivariate analysis. In study population 2 (PE), serum levels of sclerostin were not different between women with PE and controls (PE: 18.8 [9.2] pmol/l; controls: 19.3 [8.8] pmol/l; p = 0.504). Furthermore, the osteocyte-secreted factor was not related to any metabolic and gestational parameter in this cohort. Conclusions Sclerostin serum levels are not associated with an adverse metabolic profile during pregnancy in women with GDM and PE. The physiological significance of different associations of circulating sclerostin between pregnancy and non-pregnant status needs to be determined in future experiments.